KONDISI EKONOMI DAN KEHARMONISAN RUMAH TANGGA MENIKAH USIA DINI (STUDI KHASUS NAGARI SOLOK AMBAH KECAMATAN SIJUNJUNG KABUPATEN SIJUNJUNG) - Lestari, Annisa Ayu; Rahmanelli, Rahmanelli (DEPARTEMEN GEOGRAFI FIS UNP, 2024)
This study aims to find out about the economic conditions and household harmony of early marriage as well as the impact and solutions of economic conditions and household harmony who marry early in Solok Ambah Village, Sijunjung District, Sijunjung Regency. The type of research used is qualitative with a descriptive approach. Data collection techniques in this study through interview observations and documentation studies. The information in the study amounted to 14 couples and of them there was 1 divorced couple, which was obtained through purposive sampling technique. Data analysis was carried out by reducing the data presentation of the data and drawing conclusions. The validity of the data was tested by triangulation of data sources. Based on the findings in the field, it shows that (1) the economic conditions of the households of couples who marry early at an average age of 13-20 years are living independently. Still dependent on parents. Weak economy and some have been able to open their own businesses. (2) household harmony in early marriage, with an average age of 13-20 years, some have been able to maintain good communication patterns, some have not been able to maintain the integrity of the household properly and those who cannot often lead to divorce (3) the positive impact is getting more diligent work and feel more responsible while the negative impact is often the occurrence of conflicts in the household. (4) solutions that can be given are solving problems wisely and calmly, maintaining good communication patterns, receiving positive input and being grateful for the income earned.